Vascular Proteomics Methods and Protocols - Vivanco, Fernando (Methods in Molecular Biology, Methods and Protocols, 2013)
Proteomics is a rapidly expanding investigation platform in cardiovascular medicine. Driven by major improvements in mass spectrometry (MS) instrumentation and data analysis, the proteomics field has flourished in recent years particularly in the study of complex diseases. These recent advances are characterized by the development of quantitative MS-based methods that promoted the field from primarily identifying proteins to also providing measurements of relative changes in protein levels between different cell states. This progress is reflected in the application of proteomic techniques to vascular pathology. Vascular Proteomics: Methods and Protocols provides up-to-date methods and protocols for the analysis of arteries, cells, lipoproteins, body fluids, and metabolites, with a particular focus on MS-based methods of protein and peptide quantification. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Vascular Proteomics: Methods and Protocols is a representative selection of methods that can be a useful resource for experienced proteomics practitioners as well as newcomers interested in becoming acquainted with the practice of proteomic techniques for cardiovascular research